ITGB5 promotes innate radiation resistance in pancreatic adenocarcinoma by promoting DNA damage repair and the MEK/ERK signaling pathway - Wen, Xin; Chen, Si; Chen, Xueting; Qiu, Hui; Wang, Wei; Zhang, Nie; Liu, Wanming; Wang, Tingting; Ding, Xin; Zhang, Longzhen (Frontiers in Oncology, 2022)
Pancreatic adenocarcinoma (PAAD) is one of the most aggressive digestive system tumors in the world, with a low early diagnosis rate and a high mortality. Integrin beta 5 (ITGB5) is demonstrated to be a potent tumor promoter in several carcinomas. However, it is unknown whether ITGB5 participates in the occurrence and development of PAAD. In this study, we confirmed a high expression of ITGB5 in PAAD and its role in promoting invasiveness and transitivity in PAAD. Besides, the knockdown of ITGB5 increased cell sensitivity to radiation by promoting DNA damage repair and the MEK/ERK signaling pathway. Collectively, these results show that ITGB5 plays an essential role in pancreatic cancer growth and survival.